Ampliación de las posibilidades de análisis estadístico de las escalas ordinales ipsativas - Escurra Mayaute, Luis Miguel (1987)
This paper deals on the validation of the Hayes formula to obtain interval scores from ordinal ipsatives scores. To do so, the Rokeach Values Scale modified by Tueros was used. Eighty university Psychology students responded to both formats. The validity of the formula was confirmed for this population and for research purposes.